2016
DOI: 10.1007/s11365-016-0385-8
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and innovativeness of small and medium-sized construction enterprises

Abstract: The construction industry is a key industry in any economy. Due to its specific characteristics, the industry is of substantial importance to the development of other sectors. Competition is highly intense, and the industry itself is susceptible to changes in market circumstances that force the entities operating in it to continuously take actions to enhance their competitiveness by, among other things, introducing innovative solutions. The objective of the present study is to evaluate the level of innovativen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 64 publications
(66 reference statements)
0
37
1
3
Order By: Relevance
“…More specifically it plays an important role at the firm level. For example, Staniewski et al [52] suggested that a strong leadership and a highly qualified educated manager would contribute to the innovative activity of construction enterprises. The majority of researchers referred to transformational leadership and transactional leadership as the core effective leadership behavior in organizations.…”
Section: Ambidextrous Leadership and Sustainability-based Project Permentioning
confidence: 99%
“…More specifically it plays an important role at the firm level. For example, Staniewski et al [52] suggested that a strong leadership and a highly qualified educated manager would contribute to the innovative activity of construction enterprises. The majority of researchers referred to transformational leadership and transactional leadership as the core effective leadership behavior in organizations.…”
Section: Ambidextrous Leadership and Sustainability-based Project Permentioning
confidence: 99%
“…Available reports also suggest that most of the operators in the manufacturing sector are SMEs engaged in processing, production and delivery of goods [37]. Consequently, to achieve optimal economic development and to reduce dependency on crude oil for redistribution of economic wealth, the government of Nigeria seeks rescue from the SME sector by employing economic diversification [40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Elde edilen bulgular incelendiğinde fen bilimleri öğretmen adaylarının bir kısmının iletişim ve yaratıcı düşünme becerilerini belirttikleri görülmektedir. Bu becerilerin yanı sıra girişimcilik becerisine sahip olan bireylerin genellikle risk alma (Chimwai ve Munyanyi, 2019;McCarthy, Puffer ve Lamin, 2018;Zahra, 2018), vizyon sahibi olma (Ratten ve Ferreira, 2017), yenilikçi olma (Dwivedi ve Weerawardena, 2018;Staniewski, Nowacki ve Awruk, 2016;Vnoučková, 2018), rekabet üstünlüğü sağlayabilme (Kadir vd., 2017;Ogunkoya, 2018) gibi temel özellikleri de sahip olması gerekmektedir. Adayların ise çok azının bu özellikleri vurguladıkları dikkat çekmektedir.…”
Section: Discussionunclassified